PERUBAHAN SOSIAL MASYARAKAT BERPENGHASILAN RENDAH (MBR) KONSUMEN PERUMAHAN BERSUBSIDI SEBAGAI SASARAN PROGRAM PENGADAAN PERUMAHAN DAN PENGEMBANGAN KAWASAN PERMUKIMAN DI KABUPATEN SORONG - Joseph E. Lopulalan; Natasha V. Leuwol (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This research was conducted with the underlying reasons behind the development carried out to address the population problem through the construction of low-cost housing for low-income people (MBR) and the construction of residential areas in Sorong Regency based on Law Number 01 of 2011 concerning Housing and Settlement Development that has been developed Starting with the Government of Sorong Regency, cooperating with entrepreneurs in the housing sector cannot yet be carried out with the help of improving the target community of the Sorong community in general. The method used in this study is a qualitative research method with MBR research subjects subsidized housing consumers in the area of ​​Sorong Regency which already has housing units. The results of the study found that the social changes occurring in the MBR need not be sufficient to support the sustainability of development programs in the field of public housing with the MBR as a target of improving people's welfare.